2022
DOI: 10.1002/mren.202100052
|View full text |Cite
|
Sign up to set email alerts
|

5‐Ethylidene‐2‐norbornene Polymerization by α‐Diimine Nickel Catalyst: A Revealing Insight into the Pivotal Function of Binuclear and Mononuclear Catalyst Structure in Tailoring Polymer Architecture

Abstract: The present investigation is undertaken to provide a deeper understanding of the 5‐ethylidene‐2‐norbornene (ENB) homopolymerization. To this end, binuclear and mononuclear nickel α‐diimine catalysts, as well as modified methylaluminoxane (MMAO) as a cocatalyst, are selected and utilized. Al/Ni ratio of 1000 coupled with a temperature 25 °C and a polymerization time 12 h are chosen as the optimal statistics. It is shown that the highest obtained activity for binuclear and mononuclear catalysts are 511 and 478 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…It is also important to note that these distinctions originate primarily from various modes of monomer enchainment coupled with the skeleton rearrangements during polymerization. According to the 13 C NMR spectra of P(NB-M), and P(NB-B), our former studies proved that the Ni-based catalysts (BNC, MNC), by and large, perform polymerization of NB through vinyl-addition polymerization (2,3-enchainment). 14,44 Hence, it can be suggested that the presence of tethered exocyclic double bond exerts a far-reaching impact on the governing polymerization pathways.…”
Section: Dmta Analysismentioning
confidence: 71%
See 3 more Smart Citations
“…It is also important to note that these distinctions originate primarily from various modes of monomer enchainment coupled with the skeleton rearrangements during polymerization. According to the 13 C NMR spectra of P(NB-M), and P(NB-B), our former studies proved that the Ni-based catalysts (BNC, MNC), by and large, perform polymerization of NB through vinyl-addition polymerization (2,3-enchainment). 14,44 Hence, it can be suggested that the presence of tethered exocyclic double bond exerts a far-reaching impact on the governing polymerization pathways.…”
Section: Dmta Analysismentioning
confidence: 71%
“…23 The characteristic signals that are assignable to unsaturated moieties (2.4-2.8 and 5-6.2 ppm) for P(ENB-B) have been previously shown to disappear following the chemical functionalization. 13 According to spectroscopic data in this study, two probabilities, namely Scheme 6 and Scheme 7 can be proposed as probable structures of P(ENB) samples produced by BNC and MNC, respectively. Figure 8 displays the 1 H NMR spectra of ENB-NB copolymers (Table 1).…”
Section: Characterization Of Polymers By 13 C Nmr Analysismentioning
confidence: 81%
See 2 more Smart Citations
“…[ [1][2][3][4][5][6] Recent developments, metallocene-catalyzed chain-shuttling polymerizations, have facilitated expanding the range of metallocene versatility. However, only five metallocene catalysts have been kinetically studied in the literature, partly because there are no efficient methods or rapid kinetic models for obtaining necessary information, such as active site counts.…”
Section: Introductionmentioning
confidence: 99%